Dieta de Lycalopex cf. gymnocercus (Carnivora: Canidae) na zona de hibridação da espécie - Clerici, Giannina Piatto (Universidade Federal de São Carlos, 2022)
The study of the feeding habits of carnivores is essential to understand the dynamics of the ecosystems in which they are inserted, since carnivores play a fundamental role in controlling prey and, for those whose diet is omnivorous, they can also act as seed dispersers. The present study aimed to evaluate the feeding habits of individuals of pampas fox (Lycalopex cf. gymnocercus) in the hybridization zone of the species, in an agricultural area in the interior of São Paulo, being the first study with this species. in the state, since, until recently, the species was restricted to southern Brazil. Through analysis of feces collected during a year, both from adults and young, it was possible to describe the diet of individuals residing in the area of Fazenda do Zoológico de São Paulo. Adults had a more varied diet than the young, consuming 28 taxa among vertebrates, invertebrates and plant material, in addition to different anthropic materials, such as aluminum foil, rubber and textile fabric. In general, invertebrates are consumed most frequently, followed by vertebrates and plant matter. However, consumption frequencies vary over the seasons, probably according to the availability of items. The offspring consumed 13 taxa, including vertebrates, invertebrates and plant matter (in addition to anthropic material - aluminum foil), with vertebrates being the most consumed items, which is expected, since they need higher levels of protein for their development. Despite the generalist diet, the niche breadth (calculated by the Simpson index) was low, both for adults and for pups. It is possible that opportunistic habits of individuals have generated this data, since, despite consuming a wide variety of taxa, most are consumed at low frequencies, while few are consumed at high frequencies. The studied individuals seem to tolerate modified environments, being able to consume urban garbage, domestic fruits and exotic species. However, the consumption of anthropic materials brings an alert about the risks of these environments and the proximity to humans, factors that need to be better studied. Finally, it is expected that the data obtained here can help in future management and conservation strategies, since the species is not native to the state and possible impacts on native fauna and flora are still unknown.
Diet of Lycalopex cf. gymnocercus (Carnivora: Canidae) in the hybridization zone of the species
Keywords: Hábitos alimentares; Ecologia; Nicho trófico; CIENCIAS BIOLOGICAS::ECOLOGIA